(untitled) (Huellas, 2022)
This analytical work is located in the so called ‘devastated territories’. We aim at producing knowledge in relation to the subjectivation processes imposed by dispossession regimes (confiscatory, extractivist, others) as a specific type of ‘social machine’ that grants “recognition” to certain forms of life. It is important for us to know the definitions of ‘dignified life’ that emerge from the dissident territorial experience of said systems, which disputes the differential distribution of precariousness typical of the hegemonic extractive framework. We focus on experiences located in two cases of extractive territories devastated by the grid of the non-conventional hydrocarbon model (Allen) and territories of the Southern Rio Negro line linked mainly to sheep production (Sierra Colorada and Jacobacci), whose colonial order persists and deepens its impacts on community networks. We point out some territorial markings that account for the future of the system and we present experiences of dissident singularization, such as collective practices of production of the common and definitions of decent life (inhabitability) that are being built in the face of crisis systems that reverse the relationship between norm and exception.